Restoring place attachment in a ruined post-industrial landscape: change, sense of community and aesthetics in Barreiro, Portugal - Brito-Henriques, Eduardo (2022)
Place attachment in ruined post-industrial landscapes is a very controversial issue. This chapter explores this topic in Barreiro, a shrinking post-industrial town in the Lisbon metropolitan area, Portugal, that has become an effervescent spot for creativity in the very recent years. Thus, links among industrial ruination, arts and place attachment are especially explored in this chapter, looking at how this community of artists and creatives perceives and experiences the new post-industrial condition of the place. The chapter shows that even places stigmatised by toxic legacies and ravaged by de-industrialisation can generate positivities within their communities, in some sub-groups, highlighting that of artists and creatives as one of them. In fact, ruined post-industrial landscapes possess sensory qualities and material affordances that can generate unforeseen forms of creative subjectivity and stimulate renewed forms of place attachment mediated by the arts, as we conclude in this chapter. This fact also emphasizes the potential of arts and creativity for placemaking and restoring place attachments.